ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN OBESITAS TERHADAP ANAK USIA 1-5 TAHUN DI POSYANDU FLAMBOYAN SILAU MALAHA KABUPATEN SIMALUNGUN TAHUN 2020 - rading, yenni (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
In children under 5 years old, obesity is a concern of the World Health Organization (WHO) by establishing the problem of obesity as an indicator to overcome nutritional problems in children under 5 years through Sustainable Development Goals (SDGs). The study aims to determine what factors influence the incidence of obesity in children aged 1-5 years in the Posyandu Flamboyan Silau Malaha. The study used analytic surveys with cross sectional design. The population is all mothers who have children aged 1-5 years as many as 85 people. The sampling technique uses total sampling method. Data analysis was performed with univariate, bivariate with chi square and multivariate analyzes with logistic regression tests at Î± = 0.05. The results showed that gender (0,000), education (0,001), mother's occupation (0,000), maternal knowledge about nutrition (0,000), mother's attitude about nutrition (0,000), parental income (0,000), number of family members (0,000), exclusive breastfeeding (0,000) affects the incidence of obesity in children aged 1-5 years. The conclusion of this study is the influence of child sex factors, mother's education, mother's occupation, mother's knowledge about nutrition, mother's attitude about nutrition, income of parents, number of family members and exclusive breastfeeding on the incidence of obesity in children aged 1-5 years. It is recommended for mothers of toddlers to pay more attention to the nutritional status of toddlers so that the health of children aged 1-5 years can be maintained to reduce the morbidity of toddlers